Exploration and Representation of Banjarmasin’s Local Architecture and Culture in 3D Blender Animation as an Educational and Adaptation Medium for Migrants - Royd, Ivan Cavanneva; Ilmiyanor, Akhmad Hafi; Rahman, Sultan Nur; Sabrila, Trifebi Shina (INSTALL: Information System and Technology Journal, 2025)
The city of Banjarmasin, known for its unique river-based culture and traditional architecture, holds rich cultural heritage that is increasingly at risk of being forgotten, especially by younger generations who migrate to urban areas for education or work. This study explores how local architecture and cultural values of Banjarmasin can be represented through 3D animation using Blender, an open-source animation software. The aim is to develop an educational and emotional storytelling medium that reconnects young migrants with their cultural roots. The animation project, titled “Tumbuh Diantara Jarak” (Growing Between Distance), follows the story of a young man named Atma, who migrates from Java to Banjarmasin and experiences emotional and cultural transitions. The production process follows standard animation workflows, including idea development, storyboard scripting, modeling, keyframing, rendering, and editing. Blender was used to create visual assets such as traditional houses, symbolic landmarks, and culturally relevant environments like Siring. Audio elements, character voiceovers, and emotional visual cues were added during post-production using tools like KineMaster, CapCut, and Alight Motion. The results show that 3D animation is an effective tool not only for cultural preservation but also for emotional engagement and educational adaptation. The project demonstrates how digital storytelling can bridge cultural gaps and offer a meaningful medium for diaspora communities to reconnect with their heritage. Further research may explore audience reception and integration of interactive elements for deeper engagement.